An investigation into the synergistic wellbeing benefits of greenspace and physical activity: Moving beyond the mean - Ambrey, Christopher (My University, 2016)
The purpose of this study is to shed light on: (1) how greenspace and physical activity, independent of any synergy, are heterogeneously linked across the distribution of wellbeing; and also (2) how the potential synergies between greenspace and physical activity might have heterogeneous impacts across the distribution of wellbeing. Using data from the Household, Income and Labour Dynamics in Australia survey and data from Geographic Information Systems this study finds, for the case of major Australian cities, that greenspace and physical activity are independently positively associated with life satisfaction, mental health and negatively associated with psychological distress. A finding which is stronger for physical activity than it is for greenspace. Across measures of life satisfaction, mental health and psychological distress, the results lend support to the hypothesis that physical activity may be relatively more effective at mitigating the likelihood of experiencing a serious dearth of wellbeing, compared to promoting higher levels of wellbeing. Unexpectedly, the results do not provide support for the hypothesised greenspace-physical activity synergy. A result found to be common across the wellbeing distribution. While further research is required to draw a definitive conclusion, this result may indicate that physical activity is simply not conducive to the realisation of the restorative benefits of exposure to nature, and the other co-benefits of ‘green exercise’. In all, the findings presented in this study add to the existing stock of knowledge from a socialecological perspective and also raise new questions for future research. The results presented in this study may also prove useful to policy makers wrestling with the challenges of maintaining or improving residents' wellbeing and reducing residents' ill-being in the face of continuing population growth and declining per capita greenspace.
Urban Forestry & Urban Greening
Keywords: Health -- Wellbeing; Satisfaction -- Life; Health -- Mental; Health and wellbeing; Satisfaction; Health; Life; Mental; Wellbeing; Health and wellbeing